ANALISIS PENGARUH NILAI TUKAR RUPIAH, TINGKAT SUKU BUNGA SBI (BI RATE) DAN HARGA EMAS DUNIA TERHADAP INDEKS LQ45 DI BURSA EFEK INDONESIA - Miftahul Jannah; Nurfauziah Nurfauziah (Jurnal Manajemen Maranatha, 2018)
The purpose of this paper is to investigate the impact of macroeconomic on Index LQ45 in Indonesian Stock Exchange (BEI). Used data were daily report from 2011 until 2015. This study used linear regression analysis method to see the effect of exchange rate, interest rate (BI rate) and gold price on Index LQ45. Based on the results of this study, exchange rate and gold price have a positive and significant effect on Index LQ45, while interest rate (BI rate) has a negative and significant effect. Keywords: Index LQ45, Exchange rate, SBI Interest Rate (BI rate), Gold Price